26 Refractory and/or catastrophic APS in SLE. (1st September 2020) - Cervera, Ricard
Abstract : Antiphospholipid syndrome (APS) is an autoimmune disease characterised by vascular thrombosis and pregnancy morbidity in the presence of antiphospholipid antibodies (aPL), mainly lupus anticoagulant (LA), anticardiolipin antibodies (aCL) and anti-β2-glycoprotein I antibodies (anti-β2GPI). Precision Medicine can benefit the specific profiles of patients with refractory thrombotic and/or obstetric APS and those with catastrophic APS. Hydroxychloroquine and low-dose steroid, alone or combined, may be an option for pregnant APS patients with a previous pregnancy refractory to conventional therapy. Intravenous immunoglobulins and plasma exchange, alone or combined, could be considered in refractory high-risk pregnant APS patients. 1 2 Evidence on the management of recurrent thrombosis despite vitamin K antagonists (VKA) treatment is limited. After evaluating other risk factors for thrombosis (e.g., traditional cardiovascular risk factors, cancer, other thrombophilic states) and investigating the adherence to VKA treatment, increase of target international normalised ratio (INR) to 3–4, or INR 2–3 with the addition of low dose aspirin, or switching to low molecular weight heparin may be considered. Adjunctive therapy with antimalarials or statins could also be considered. Management of catastrophic APS is challenging. The higher recovery rate is achieved by the combination of anticoagulation, plus glucocorticoids, plus plasma exchange and/or intravenous immunoglobulins. New therapeutic approaches include rituximab and eculizumab. Learning Objectives: Explain the main unmet needs in the management of the APS in SLE Describe the options for the treatment of refractory thrombotic and obstetric manifestations of APS Discuss the current recommendations for the management of catastrophic APS cases Discuss new trends in research on new therapies for APS References: Tektonidou MG, Andreoli L, Limper M, et al . EULAR recommendations for the management of antiphospholipid syndrome in adults. Ann Rheum Dis 2019:annrheumdis-2019-215213. Rodríguez-Pintó I, Espinosa G, Erkan D, et al . The effect of triple therapy on the mortality of catastrophic anti-phospholipid syndrome patients. Rheumatology (Oxford) 2018;57(7) :1264–70.